Pengaruh Adsorben Terhadap Pembentukan Na2CO Berbasis CO23 Hasil Pembakaran Tempurung Kelapa - Weny Eka Rosaline, Simon Sembiring, Wasinton Simanjuntak (Jurnal Teori dan Aplikasi Fisika, 2013)
A research synthesis of sodium carbonate (Na2 CO) using NaOH solution of technical and combustion CO2 from burning coconut shell with adsorbent rice husk, activated carbon, zeolite. Na2CO3 precipitate obtained from a mixture of technical solution of NaOH and CO2 from burning coconut shells. Na2CO3 precipitated cleaned with 70% alcohol. Precipitate was filtered and vacuumed. Heating is then performed at a temperature of 110oC for 6 hours to remove moisture content. Once dried, crushed and weighed samples. Precipitated of adsorbent rice husk, activated carbon, zeolite respectively 24 grams, 17.5 grams, and 5.5 grams. The samples were characterized using FTIR and showed a group CO3 2- Groups CO3 2- in the sample of adsorbent rice husk is at number 1448.74 cm -1 and 866.06 cm -1. Group CO3 2- in the sample of adsorbent activated carbon is at 881.25 cm-1 numbers. Cluster CO3 2- in the sample of adsorbent zeolite is at number 866.35 cm -1. Keyword: Sodium Carbonate, Adsorbent, Carbondioxide, Coconut Shell.